Penggunaan Powerpoint Game Pada Pembelajaran Lingkaran di Kelas VIII SMP Negeri 1 Tanjung Raja - Oktaviani, Sherly; Santoso, Budi; Hiltrimartin, Cecil (Mathematics Education Journal, 2017)
The purpose of this study is to know the implementation, motivation and achievement of the eight grade students of SMP Negeri 1 Tanjung Raja in circle learning through PowerPoint Games. To collect the data observation, questionnaires and tests were used. The result of study showed that the implementation of learning through PowerPoint Games was very successful in terms of teacher’s activities and the activities of the students. In addition, the use of PowerPoint Games motivated students. 19 out of 24 students had very high motivation (79,17%) and 5 out of them had high motivation (20,83%). After using educational games, students outcomes were good in terms of attitudes, skills and knowledge in which the average of percentage was >80% based on the assessment of curriculum 2013.